Aetiological Pattern of Haemoptysis in a Tertiary Level Hospital in Bangladesh (TAJ: Journal of Teachers Association, 2010)
To identify the causes of haemoptysis and to diagnose the diseases clinically and cost effective laboratory investigations in our situation. Fifty consecutive cases of haemoptysis admitted at Rajshahi Medical College Hospital, Rajshahi during 2000-2001 were prospectively studied .Pulmonary tuberculosis was the commonest found in 19 (38%) cases. Tuberculer bacilli could be isolated in 5 (26.31%) of the cases. Eight (16%) patients were mitral valvular diseases . Bronchial carcinoma was 4(8%) of the series. Three patients (6%) were lung abscess. Six patients (12%) had bronchiectasis. Five patients (10%) had pneumonia. Remaining five (10%) patients were miscellaneous aetiology. In the present series it has been found that pulmonary tuberculosis and mitral valvular disease comprise 54% of the cases. Chest X-ray and sputum examination were found to be the two most useful investigations necessary for aetiological diagnosis of haemoptysis. Within limited resources the aetiological diagnosis of haemoptysis can easily be done in the majority of cases by doing chest X-ray and sputum examination in our country. DOI: 10.3329/taj.v22i1.5015 TAJ 2009; 22(1): 22-25